ROTATED RECTANGULAR SLOTS AND MIRRORED INVERSED CANTOR-SETS ON ULTRAWIDEBAND ANTIPODAL VIVALDI ANTENNA - Sabri Alimi; Teguh Prakoso; Munawar Agus Riyadi (SINERGI, 2019)
Variants of antipodal Vivaldi antenna (AVA) design suitable for access point working on 0.5 – 6.0 GHz are proposed in this paper. The novel designs were produced by employing three novel techniques to conventional AVA: (i) rotated-slot pattern to shift down the frequency cutoff and enhancing bandwidth, (ii) curve design to miniaturize rotated-slot-inserted antipodal Vivaldi, and (iii) fractal-director (Cantor set) to increase the gain of antipodal Vivaldi. Using FR4 (relative permittivity of 4.4) with an overall dimension of 300 mm x 143 mm x 1.6 mm the antenna designs are able to work at a frequency of 0.472 GHz to higher than 6 GHz with a maximum gain of 11.9 dBi.